Increased fracture risk in Parkinson's disease – An exploration of mechanisms and consequences for fracture prediction with FRAX - Schini, M.; Bhatia, P.; Shreef, H.; Johansson, H.; Harvey, N.C.; Lorentzon, M.; Kanis, J.A.; Bandmann, O.; McCloskey, E.V. (Bone (New York, N.Y.), 2023)
The relative contributions of factors such as muscle strength, falls risk and low bone mineral density (BMD) to increased fracture risk in Parkinson's Disease (PD) were examined in an analysis of 5212 community-dwelling women age 75 years or more recruited to a randomised, double-blind, placebo-controlled study of the oral bisphosphonate, clodronate. Similar number of PD and non-PD subjects received treatment. Each participant had measurements of hip and forearm BMD, muscle strength (hand grip strength and maximum isometric quadriceps strength), ability in the sit-to-stand test, and postural stability. Incident radiographic and/or surgically verified fractures, and deaths, were recorded over an average follow-up of 3.8 years. A diagnosis of PD was made if it was self-reported and appropriate medication was recorded at the study entry. 47 of the women (0.9 %) had a diagnosis of PD at baseline. They were of similar age to those without PD, but reported higher disability scores and lower quality of life. While BMD at the forearm and hip regions was lower in PD, this only reached statistical significance at the femoral neck (0.61 ± 0.12 vs 0.65 ± 0.12 g/cm2, p = 0.037). Right hand grip strength was non-significantly lower in PD, but maximum right quadriceps strength was much reduced (96.9 ± 49.3 vs 126.3 ± 59.2 N, p = 0.003). Eleven (23.4 %) of the women with PD sustained 12 fractures, while 609 women (11.8 %) without PD sustained 742 osteoporotic fractures. The risk of osteoporotic fracture associated with PD was 2.24-fold higher in women with PD (Cox-regression HR 2.24, 95 % CI 1.23–4.06) and this remained high when adjusted for death as a competing risk (2.17, 95 % CI 1.17–4.01, p = 0.013). Following adjustment for femoral neck BMD, PD remained a significant predictor of fracture (HR 2.04, 1.12–3.70, p = 0.020). Entering PD as a risk variable using the rheumatoid arthritis input as a surrogate resulted in a reduction in PD as a FRAX-independent risk factor, particularly when BMD was included in FRAX (1.65, 95 % CI), but the relationship between PD and fracture risk appears to remain of clinical significance. The study suggests that PD may be an independent input in future iterations of FRAX, possibly due to non-skeletal components of risk such as reduced lower limb muscle strength. Introducing measures of muscle strength and performance in FRAX could also be considered. •FRAX may underestimate fracture risk in older women with Parkinson's disease (PD).•Lower limb muscle strength rather than low BMD may drive PD fracture risk.•Using rheumatoid arthritis as PD surrogate reduces fracture risk underestimation.•Diseases like PD require consideration for inclusion in future iterations of FRAX.